Determining Relationships Amongst Morphine, Capsule and Oil Yield Using Path Coefficient Analysis in Poppy (Papaver somniferumL.) - OZTURK, OZDEN; GUNLU, HAKAN (Asian Journal of Chemistry, 2010)
In this paper, morphine content, oil content, seed yield, capsule yield, oil yield and morphine yield were determined for four poppy cultivar, grown according to the randomized complete blocks in a split-plot design with 4 replications in Central Anatolia. Statistically significant variations were found by ANOVA amongst the genotypes for all the variables examined. The morphine, capsule and oil yield of poppy cultivars vary between, Kocatepe-96 4.12 kg ha-1, 805.6 kg ha-1, 42.88 kg ha-1; Karahisar-96 5.64 kg ha-1, 863.6 kg ha-1, 55.61 kg ha-1, respectively. Correlations amongst the variables as well as their direct and indirect effects on morphine, capsule and oil yield were also calculated using the correlation and path coefficients analyses, respectively. Positive and significant relationships were found statistically between (a) morphine yield and morphine content, seed yield, capsule yield, oil yield; (b) between seed yield and capsule yield, oil yield and (c) between capsule yield and oil yield. Path coefficient analyses indicated that morphine content (77.86 %), capsule yield (83.73 %), seed yield (10.30 %) and oil yield (1.89 %), had a positive direct effect on morphine yield.